Preparation of metal-free BP/CN photocatalyst with enhanced ability for photocatalytic tetracycline degradation. (March 2022) - Jin, Dexin; He, Dongyang; Lv, Yihan; Zhang, Kangning; Zhang, Zhaocheng; Yang, Hao; Liu, Chuanhao; Qu, Jiao; Zhang, Ya-nan
Abstract: The successful application of photocatalysis in practical water treatment opreations relies greatly on the development of highly efficient, stable and low-cost photocatalysts. The low-cost metal-free photocatalyst made up of black phosphorus (BP) and graphitic carbon nitride (CN) was successfully constructed and firstly used for the photocatalytic treatment of antibiotic contaminants in this work. Compared with bare CN, the BP/CN photocatalyst exhibited the enhanced photocatalytic performance for tetracycline hydrochloride (HTC) degradation, that 99% of HTC was removed by 6BP/CN (doping amount of BP was 6%) within 30 min under the simulated visible-light irradiation. The efficiency was even comparable to those of some high-efficiency photocatalysts recently-reported such as Fe 0 @POCN, CuInS2 /Bi2 MoO6 and Cu2 O@HKUST-1. Under natural sunlight illumination, the determined apparent rate constant for degradation of HTC by BP/CN was 2.7 times as that by P25 TiO2 . The experimental results indicated that loading BP on CN could enhance the separation of charge carriers and promote the ability of light absorption for visible-light, thus leading to a greater catalytic activity. Meanwhile, the influences of different operating variables (pH, water, ion and HTC concentration) on HTC degradation were studied in detail. Furthermore, the degradation pathway of HTC was also proposed. In addition, the photocatalytic activity of the BP/CN for production of hydrogen peroxide (H2 O2 ) was also studied, which could reach up to 501.04 μmol g −1 h −1 . It is anticipated that BP/CN photocatalyst could be used for practical water treatment. Graphical abstract: Image 1 Highlights: Metal-free BP/CN was synthesized by a simple method. 99% of HTC could be degraded by BP/CN within 30 min of visible-light irradiation. The ability of BP/CN under real sunlight irradiation was better than P25 TiO2 . The H2 O2 production efficiency of BP/CN reached up to 501.04 μmol g −1 h −1 .